STUDY OF BLOOD LIPIDS, CORTISOL AND HAEMODYNAMIC VARIATIONS UNDER STRESS IN MALE ADULTS - Qureshi, Ghulam Mujadid; Seehar, Ghulam Mustafa; Zardari, Mevo Khan; Pirzado, Zafar Ali; Abbasi, Siraj Ahmed (Journal of Ayub Medical College Abbottabad, 2009)
Background: Increased cholesterol in blood plays the role in atherosclerosis formation. It is observed that stress increases cholesterol level. Most of previous studies were conducted on biological risk factors like blood lipids under stress in middle aged persons who remained under investigations for heart problems. Objective: The study was conducted to evaluate the changes in blood lipids and blood cortisol along with sympatheo-adnergic responses determined by selected haemodynamic parameters during psychological stress. Methods: Male participants (n=114) were randomly selected. They were examined two times, for stress task of viva-voce (degree examination) and during non-stress period. Final selection of participants was depending on stress assessment and their well being. Results: Cortisol, systolic and diastolic blood pressures (SBP and DBP) and heart rate (HR) were significantly increased during stress period with p<0.001 for each parameter. But different blood lipids levels (TC, LDL-C, HDL-C and TG) were detected with different significant levels. The correlations of changed lipids with raised findings of haemodynamics and cortisol were also evaluated. Conclusion: Further studies in our population are needed to evaluate the relation of changes in various biological risk factors including IL-9 and sympatho-adernergic activities with stress factors related to our social/ environmental problems, especially genetically based psychological factors. Keywords: Cholesterols, Haemodynamics, Cortisol, psychological stress.